PENERAPAN METODE PEMBELAJARAN KONTEKSTUAL BERWAWASAN SETS DALAM MENINGKATKAN PERAN SERTA DAN PRESTASI BELAJAR EKONOMI SISWA KELAS X2 SMA NEGERI KARANGPANDAN TAHUN PELAJARAN 2015/2016 - Tegas, Tegas (Jurnal Pendidikan Ilmu Sosial, 2016)
The research aims were: 1) to explore the effectiveness of implementation contextual method based on Sets in order to improve the student’s participation economic learning. 2) To examine the effect of using the contextual method based on Sets toward the learning outcome of grade X.2 students of SMA Negeri (State Senior High School) of Karangpandan academic year 2015/2016. This was an action research conducted in two cycles. The conclusions were: 1) the implementation of the contextual method based on Sets improved the student’s participation in economic learning. This result could be inferred from the improvement of students asked frequently, the inclining of collaboration, and the capability of answering the questions. 2) The implementation of the contextual method based on Sets upgraded economic learning outcome. This conclusion was based on the student’s average score in the first cycle was 6,69, increase 0,49 than before. Furthermore, the assignment score also increase from 6,81 to 7,04 and the average daily test score was 7,44. In the second cycle, the student’s average score was 7,68 higher 0,99 than the score in the first cycle. The average of assignment score also improved from 7,04 to 7,44. In the last, 88,9% achieved the higher than the minimum score (KKM).Keywords: implementation contextual method, Sets method, affective, learning achievement